Main Priorities in Value Added Improvement-Based on Commodity Processing System - Nihayah, Dyah Maya; Pujiati, Amin; Khoiruddin, Moh (Universitas Negeri Semarang, 2017)
The huge number of rambutan plants in Gunungpati has resulted in the decline of rambutan sales price during harvest season, i.e. Rp 1,500.00 per pack, any unsold rambutan tends to immediately wilt, break and deteriorate. This research is aimed to the sequence of commodity processing priority in order to increase the product’s value-added. This study is an action research, using descriptive statistic and Analytical Hierarchy Process (AHP). The results indicate that a counseling since production until post-harvest becomes the highest priority, followed by produce sorting, and availability of produce processing technology. It is necessary to have practical field-based initiatives of businesses farmers who have managed to do the innovations, competitive advantage, and then to rise the competitiveness. To make this value-added-based horticulture commodity processing system work, Government role is required to guiding and evaluating every policy priorities.